Optimalisasi Manajemen Masjid Nurul Iman Dalam Meningkatkan Kegiatan Keagamaan Bagi Masyarakat Di Desa Manggar Raya Kecamatan Tanjung Lago Kabupaten Banyuasin - Marjuliani; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "Optimizing Mosque Management in Increasing Religious Activities for the Community in Manggar Raya Village, Tanjung Lago District." There are two research objectives, namely first to determine the optimization of management of the Nurul Iman Mosque in increasing religious activities for the community in Manggar Raya Village, Tanjung Lago District, Banyuasin Regency, secondly, to determine the supporting and inhibiting factors for optimizing the management of the Nurul Iman Mosque in increasing religious activities for the community in Manggar Raya Village, Tanjung Lago District, Banyuasin Regency. This type of research (field research) uses a qualitative approach. There are two data sources used, namely primary and secondary data sources. Data collection techniques through observation, interviews and documentation. The data analysis technique uses the Miles and Huberman concept with three stages, namely Data reduction, Data display, Conclusion drawing/verification. The theory in this research uses the theory of Moh E. Ayub, et al. The results of this research are that mosque management at the Nurul Iman Mosque is not yet optimal because the activities carried out by the mosque have not been fulfilled, due to a lack of human resources and some of them are no longer active in carrying out their duties as administrators, one of the reasons is that they are elderly so in carrying out activity programs is not optimal, and there is a lack of socializing in the community. Meanwhile, the religious activities carried out at the Nurul Iman Mosque only pray five times a day and Friday prayers, but religious activities are also carried out such as celebrating Islamic holidays, namely the Prophet's birthday, Isra Miraj, Hijri New Year, Eid al-Fitr, Eid al-Adha, mother-in-law recitation. mothers, Pahing Sunday recitation, hadroh training for mosque teenagers, and BTA for children. The supporting factors at the Nurul Iman Mosque are adequate facilities, sufficient financial support, strategic location, while the inhibiting factors for mosque management at the Nurul Iman Mosque are lack of human resources, lack of interest from the younger generation, having other activities outside of mosque activities. , the activity program is lacking.